Synthesis and Antimicrobial Screening of Three Triazole Derivatives - Morshed, MH; Islam, MF; Yousuf, MA; Hossain, GMG; Khanam, JA; Salam, MA (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Due to the medicinal importance of triazole derivatives, the antimicrobial property of three synthesized triazole derivatives were screened in vitro against some Gram positive and Gram negative pathogenic bacteria and some pathogenic fungi. In this study, three compounds 2-(5-mercapto-4-phenyl-4H-[1,2,4] triazole-3-yl]-cyclohexa- 1,5-dienol (S1), 2-[5-mercapto-4-(2-mercapto-phenyl)-4H- [1,2,4] triazole-3-yl]-phenol (S2) and 4-[3-(2-hydroxyphenyl)- 5-mercapto-[1,2,4] triazole-4-yl]-benzene sulfonamide (S3) have been synthesized. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were assessed by serial dilution technique. The compounds showed moderate antimicrobial activity against all the tested organisms and the results are comparable to standard antibiotic kanamycin. The MIC values of the compounds were found to be in the range of 16 64μg/ml. The low MIC and MBC values and high sensitivity of pathogenic microorganisms to the compounds led to conclude that the triazole derivatives have potential antimicrobial properties. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10014 DUJPS 2011; 10(1): 43-47